Determinants of Hypertension in the Elderly at Tangkahan Durian Health Center, Langkat, North Sumatra - Syafran Arrazy; Arini Fajriani; Permata Amalia Mursyid; Sumiati Sumiati; Mutia Azuba; Yunita Warina (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
Hypertension is the number one cause of death in the world every year and the most patients diagnosed with hypertension in Indonesia are the elderly, with 56.5% men and 43.5% women. The purpose of this study was to determine the risk factors associated with the incidence of hypertension in the elderly at Tangkahan Durian, Community Health Center Langkat. This research is a quantitative study with a cross-sectional approach. The sample in this study were 81 elderly people in the work area of the health center Bivariate analysis using the chi square test. The results showed that 56 people (74.4%) of the elderly suffered from hypertension. Bivariate analysis showed that there was an association between the variables of routine examination of hypertension (hypertension control), routine consumption of hypertension drugs and smoking status with p-values of 0.004, 0.001, and 0.0043 respectively. Furthermore, there was no association between genetic factors, nutritional status, stress levels and socioeconomic status with p-values of 0.143, 1.000, 0.969 and 0.973 respectively. This study suggests the local government to increase public awareness especially in routine examination, regular medication consumption and prevent smoking. Keyword: Determinants, Hypertension, Elderly, Indonesia